2012
DOI: 10.1155/2012/976972
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Adhesion and Regulation of Biofilm-Related Genes in Different Clones ofStaphylococcus aureus

Abstract: Clinical information about genotypically different clones of biofilm-producing Staphylococcus aureus is largely unknown. We examined whether different clones of methicillin-sensitive and methicillin-resistant S. aureus (MSSA and MRSA) differ with respect to staphylococcal microbial surface components recognizing adhesive matrix molecules (MSCRAMMs) in biofilm formation. The study used 60 different types of spa and determined the phenotypes, the prevalence of the 13 MSCRAMM, and biofilm genes for each clone. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
101
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 20 publications
(27 reference statements)
15
101
0
1
Order By: Relevance
“…Catheter and blood stream Staphylococcal infections play an important role in biofilms (25,26). We confirmed no significant difference between MSSA and MRSA isolates of S. aureus regarding the presence of icaADBC genes, similar to survey Atshan et al (27), in which icaADBC genes were compared between MRSA and MSSA. Furthermore, we previously observed that most isolates belonged to accessory gene regulator (agr) group I (28), but the relationship of agr groups and icaADBC expression needs more studies.…”
Section: Discussionsupporting
confidence: 91%
“…Catheter and blood stream Staphylococcal infections play an important role in biofilms (25,26). We confirmed no significant difference between MSSA and MRSA isolates of S. aureus regarding the presence of icaADBC genes, similar to survey Atshan et al (27), in which icaADBC genes were compared between MRSA and MSSA. Furthermore, we previously observed that most isolates belonged to accessory gene regulator (agr) group I (28), but the relationship of agr groups and icaADBC expression needs more studies.…”
Section: Discussionsupporting
confidence: 91%
“…There are several methods for the quantification of biofilm formation [29], but there is still no standard protocol for the detection of biofilm production. Although various methods are currently used for this purpose, the most widely used assay for evaluation of biofilm formation is the microtiter plate method [13].…”
Section: Discussionmentioning
confidence: 99%
“…The microtiter plate method was conducted as previously described [13]. Briefly, 200 µlof bacterial suspension grown in trypticase soy broth (TSB), supplemented with 1% glucose and diluted.…”
Section: Microtiter Plate Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, thermal profile for icaA gene concluded at 94ᵒC (five minutes), followed by 30 cycles at 94ᵒC (one minute), 52ᵒC (30 seconds) and 72ᵒC (1.5 minute) with final extension at 72ᵒC (10 minutes). The annealing temperature for icaB, icaC and icaD was set at 55ᵒC for one minute (16). The DNA of the positive control isolate for the genes was kindly provided by Dr. Ghaznavi Rad.…”
Section: Dna Amplificationmentioning
confidence: 99%